If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2h + -5)(4h + -3) = 0 Reorder the terms: (-5 + 2h)(4h + -3) = 0 Reorder the terms: (-5 + 2h)(-3 + 4h) = 0 Multiply (-5 + 2h) * (-3 + 4h) (-5(-3 + 4h) + 2h * (-3 + 4h)) = 0 ((-3 * -5 + 4h * -5) + 2h * (-3 + 4h)) = 0 ((15 + -20h) + 2h * (-3 + 4h)) = 0 (15 + -20h + (-3 * 2h + 4h * 2h)) = 0 (15 + -20h + (-6h + 8h2)) = 0 Combine like terms: -20h + -6h = -26h (15 + -26h + 8h2) = 0 Solving 15 + -26h + 8h2 = 0 Solving for variable 'h'. Factor a trinomial. (3 + -4h)(5 + -2h) = 0Subproblem 1
Set the factor '(3 + -4h)' equal to zero and attempt to solve: Simplifying 3 + -4h = 0 Solving 3 + -4h = 0 Move all terms containing h to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -4h = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -4h = 0 + -3 -4h = 0 + -3 Combine like terms: 0 + -3 = -3 -4h = -3 Divide each side by '-4'. h = 0.75 Simplifying h = 0.75Subproblem 2
Set the factor '(5 + -2h)' equal to zero and attempt to solve: Simplifying 5 + -2h = 0 Solving 5 + -2h = 0 Move all terms containing h to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2h = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -2h = 0 + -5 -2h = 0 + -5 Combine like terms: 0 + -5 = -5 -2h = -5 Divide each side by '-2'. h = 2.5 Simplifying h = 2.5Solution
h = {0.75, 2.5}
| -7u^2-19u-10=0 | | -7(-3xy)= | | 3(2z-4+2)=5(-3z+2) | | 2k-5/-95 | | -6cos^2x+3senx+4=0 | | 5t-13t=40 | | 0.3a+0.25=1 | | t-24=-29 | | -u+99=161 | | X-0.1x=72000 | | -4x-9=8x+15 | | 10a+5=7 | | 3x+2=228 | | -9=-y | | -7*3x^3= | | q^3-2q^2=500 | | 11+5x=-14 | | 12M-6M+11=6M+16 | | -6(4p+4)-28=4(3p+5) | | y-15.53=-8.53 | | X+x-47770=296770 | | 6.5y=45.5 | | 2x-47770=296770 | | 2x=6+20 | | (d^4+2d^3-3d^2)y=x^2+3e^2x+4sinx | | 9/2x-3/2=15/2 | | 6-7n+4n=22-91 | | y-1=-7/8 | | X/.9=90 | | -68+3y+9=2(5y-2)-6 | | 3(4x-8)+7=12x-17 | | 6/5-5x=4 |